MAPPING ON ANALOGICAL REASONING TOPIC LIMIT FUNCTION: WITH AND WITHOUT INTERMEDIATE PROBLEMS - Radja Nauval Arie Salim; Abdul Haris Rosyidi (Program Studi S1 Matematika UNESA, 2022)
Abstrak Mapping adalah tahapan penting pada penalaran analogi, namun banyak ditemukan kesalahan pada prosesnya. Mapping merupakan proses menemukan sebuah kesimpulan dari hubungan yang ada pada masalah sumber dan masalah target. Salah satu materi matematika SMA yang sering terjadi kesalahan pada proses pengerjaannya adalah limit fungsi trigometri. Penilitian ini bertujuan untuk menganalisis mapping siswa SMA pada penalaran analogi dengan dan tanpa masalah antara pada materi limit fungsi trigonometri. Metode penelitian yang digunakan adalah kualitatif. Subjek penelitian ini adalah 4 siswa kelas XII MIA SMA swasta di Gresik, dengan rincian 2 siswa menyelesaikan soal mapping penalaran analogi dengan masalah antara, dan 2 siswa menyelesaikan soal mapping penalaran analogi tanpa masalah antara. Data dianalisis menggunakan tahapan mapping yaitu mengidentifikasi hubungan masalah sumber dan masalah target, mengidentifikasi suatu struktur masalah sumber yang sesuai dengan masalah target dan menggunakan masalah sumber ke masalah target. Hasil penelitian menyimpulkan bahwa pada mapping, siswa kesulitan pada tahapan mengidentifikasi hubungan masalah sumber dengan masalah target. Siswa yang berhasil mengidentifikasi hubungan masalah sumber dan masalah target dapat mengidentifikasi kesamaan struktur dan mengetahui cara menggunakan masalah sumber ke masalah target, sedangkan siswa yang tidak berhasil mengidentifikasi hubungan masalah sumber dan masalah target tidak dapat melanjutkan ke tahapan selanjutnya. Pemberian masalah antara dapat membantu siswa dalam mengidentifikasi hubungan masalah sumber dan masalah target, sehingga masalah antara dapat digunakan sebagai jembatan masalah sumber ke masalah target. Kata Kunci: Limit fungsi, Mapping, Masalah Antara Penalaran Analogi Abstract Mapping is an important step in analogical reasoning, but many errors are found in the process. Mapping is the process of building conclusions from the relationship between the source problem and the target problem. One of the high school mathematics materials that often makes mistakes in the process is the limit of trigometric functions. This study aims to analyze the mapping of high school students on analogical reasoning with and without intermediate problems on the limit material of trigonometric functions. The research method used is qualitative by using 4 subjects who are class XII students of MIA private high school in Gresik, with details of 2 students solving analogy reasoning mapping problems with intermediate problems, and 2 students completing analogue reasoning mapping problems without intermediate problems. The data were analyzed using the mapping stage, namely identifying the relationship between the source problem and the target problem, identifying a source problem structure that is in accordance with the target problem and using the source problem to the target problem. The results of the study concluded that in mapping, students had difficulty at the stage of identifying the relationship between the source problem and the target problem. Students who succeed in identifying the relationship between the source problem and the target problem can identify structural similarities and know how to apply the source problem to the target problem, while students who fail to identify the relationship between the source problem and the target problem cannot proceed to the next stage. Giving intermediate problems can help students identify the relationship between the source problem and the target problem, so that the intermediate problem can be used as a bridge between the source problem and the target problem. Keywords: Analogical Reasoning, Fungsion Limit, Intermediate Problems, Mapping